Appropriation of ICT as an instrument of human development - Reyes García, Pedro; Fuentealba Acuña, Anibal (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
In this article, we will delve into the role of information and communication technologies in the human development of Internet users, neighbours and participants in social organizations of small towns far of big cities in Chile. As a theoretical framework we rely on the postulates of Serge Proulx and Amartya Sen. We use a qualitative approach and as a methodological tool the semi-structured interview. Among the main findings are the undisputed assessment of the Internet as a tool for communication and access to information, which impulses the leaders to promote its use; Internet as a tool for learning and organizing daily work. Likewise, technology is valued as a link with the political and administrative authorities of the location where users live.
Keywords: Human Development; Appropriation; TIC